2015
DOI: 10.1098/rstb.2014.0291
|View full text |Cite
|
Sign up to set email alerts
|

Estimating T-cell repertoire diversity: limitations of classical estimators and a new approach

Abstract: A highly diverse T-cell receptor (TCR) repertoire is a fundamental property of an effective immune system, and is associated with efficient control of viral infections and other pathogens. However, direct measurement of total TCR diversity is impossible. The diversity is high and the frequency distribution of individual TCRs is heavily skewed; the diversity therefore cannot be captured in a blood sample. Consequently, estimators of the total number of TCR clonotypes that are present in the individual, in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
184
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(186 citation statements)
references
References 97 publications
2
184
0
Order By: Relevance
“…We performed sequencing on CD4 + and CD8 + T cells separately, allowing for key comparisons between the 2 distinct repertoires. Consistent with prior studies (20,22), the alloreactive populations were not only composed of large numbers of unique clones ( Figure 1A), but were also qualitatively diverse in terms of CDR3 amino acid length and Vβ-and Jβ-gene usage. Since the structure of the TCR is determined in part by the number of amino acids that gives rise to the CDR3 region, we compared the distribution of CDR3 amino acid lengths between the unstimulated and alloreactive populations and found no significant difference (Figure 2, A and B, and Supplemental Figure 3).…”
Section: Identification and Qualitative Characterization Of Human Allsupporting
confidence: 74%
See 1 more Smart Citation
“…We performed sequencing on CD4 + and CD8 + T cells separately, allowing for key comparisons between the 2 distinct repertoires. Consistent with prior studies (20,22), the alloreactive populations were not only composed of large numbers of unique clones ( Figure 1A), but were also qualitatively diverse in terms of CDR3 amino acid length and Vβ-and Jβ-gene usage. Since the structure of the TCR is determined in part by the number of amino acids that gives rise to the CDR3 region, we compared the distribution of CDR3 amino acid lengths between the unstimulated and alloreactive populations and found no significant difference (Figure 2, A and B, and Supplemental Figure 3).…”
Section: Identification and Qualitative Characterization Of Human Allsupporting
confidence: 74%
“…Based on approaches developed in ecology to study population diversity, different strategies have been proposed to address the unseen species question (14,22). Here we present a new computational approach to model T cell clonal frequency distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Further variability and antigen recognition capacity is introduced by nucleotide insertion (NI) in the recombined TCR a and b VDJ sequences. This generates a vast T-cell repertoire, yielding in excess of a trillion potential TCRab combinations capable of reacting to non-self (and self) peptides [3]. Since the advent of next generation sequencing techniques, the TCR repertoire, as estimated by TCR b clonal frequency measurement has revealed that the T-cell repertoire in healthy individuals is complex with thousands of clones in each individual spanning a spectrum of high and low frequencies [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with the findings reported previously by other groups. 32,33 Spectratyping assays have been widely used in clinical settings for more than a decade to detect the TCR clonality of patients. This method separates V/D/J DNA clones based on the DNA amplicon size in the TCR repertoire.…”
Section: Variability Across Different Biological Replicate Librariesmentioning
confidence: 99%